The Analysis of Stock Price in Tourism Industry Listed in Indonesia Stock Exchange 2012-2016 - Novita Kristiana Angela; Yunita Ismail Masjud (JAAF (Journal of Applied Accounting and Finance), 2018)
The tourism industry showed rapid growth from year to year, but sales in some tourist companies were declined. This study was analyzed the stock price of tourism companies listed in Indonesia Stock Exchange from 2012-2016. There were PT Bukit Uluwatu Villa Tbk, PT Destinasi Tirta Nusantara Tbk, PT Jakarta International Hotels and Development Tbk, and PT Bayu Buana Tbk. This study conducted to prove the significant partially and simultaneously influenced of debt equity ratio (X1), current ratio (X2), earning per share (X3), price to book value (X4), and return on asset (X5) towards the stock price (Y). In addition, this research also identified the most significant influence factor towards the stock price. Data collection method was purposive sampling and got 80 observations from 4 companies in 5 consecutive years (2012-2016) which fulfilled the criteria. This research adopted quantitative research with multiple regression analysis. The result showed that from 5 independent variables, DER had negative significant to the stock price, CR had negative significant to the stock price, EPS positive significant to the stock price, PBV positive significant to the stock price, and ROA negative significant to the stock price. DER, CR, EPS, PBV, and ROA simultaneously had a significant relationship to the stock price. In summary, EPS and PBV is the variable that had the strongest influence to the stock price of tourism industry.